Bagaimana Komitmen Organisasi Dipengaruhi oleh Work Family Conflict, Stres Kerja dan Kepuasan Kerja Sebagai Prediktor - Andhi Supriyadi; Ray Octafian; Dwi Ermayanti Susilo (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
Human resources as a resource is the company's most important asset, human resources are always expected to give maximum level of contributions and committed to the company to reach expected goals. Employees who are committed to their organization will take risks to the organization and want to remain in the organization. This research is done to explore impact of work family conflict, job stress and job satisfaction to organizational commitment. The response taken was 138 employees of a garment factory in the Semarang Regency area. With SPSS analysis technique version 23. Result of the research found work family conflict and work stress have negatively impact and insignificant to organizational commitment. And job satisfaction has a positively impact and significant to organizational commitment. Simultaneously work family conflict, job stress and job satisfaction have a significant influence to organizational commitment.